Modelación matemática para estimar Oxígeno disuelto en el Agua, en función de las características físicas del cauce del Río San Pablo, Cantón La Maná Provincia de Cotopaxi, durante el periodo octubre 2018-agosto 2019. - Pastuña Maza, Byron Javier (2019)
The main purpose of this research is to estimate the existing oxygen in rivers by its physical condition. A mathematical modeling was applied to the oxigen estimation disjoint in the function of the predominant physical characteristics in a river. This model is based on the convection phenomenon - diffusion by the gas law, applying the Henry law and the dimensional analisis application. The model uses speed, re-aeration, function error, coefficient of molecular diffusion and gases law. For the conversion of g/cm to mg/L, in the convection – difusión phenomenon is completed the LMT-1 dimensional analysis. The results were obtained through topography, scientific observation and cross-sectional design. During the dry weather data collection was taken. Result is the most influential variable in dissolved oxygen concentration is the water slide height, but at that time the concentration decreases, but the lower height increases the concentration. comparing the model product data I have had a broader results overview, if you have data from a disjoint oxygen team for discussion. The model Validation by the NASH coefficient with a value of -0.2% indicates that the displaced oxygen should be predicted according to the calculated data. It is advisable to perform data collection at the time of avenue.